Breakbeat Culture and Identity in Andalusia: The Role of Instagram in Representing a Marginal Scene - García-López, Estrella (Cuadernos de Documentación Multimedia, 2026)
Since the 1990s, breakbeat—a subgenre of electronic dance music—has become established in Andalusia, driven by the influence of British tourism on the Costa del Sol, and has given rise to a subcultural scene within the national music landscape. From a perspective that incorporates techniques from communication studies, social sciences, and ethnomusicology, this article examines several factors that highlight the identity-related significance this music holds for a segment of the Andalusian population. Through content analysis of audiovisual publications (reels) on Instagram accounts during 2023 and 2024, the study explores the ways in which this community constructs its own narratives, visualizes its practices, and redefines its position within the contemporary soundscape.